An Effort to improve the effectiveness and efficiency of corn farmers' production in Sidomulyo Village, Samarinda - Sihombing, Ruspita; Fatmawati, Anni; Lia, Rakhel (Community Empowerment, 2021)
Corn farming communities in the Anggana sub-district usually harvest dry corn every 2-3 months and resulting about 200-700 kg. However, there are a very limited number of corn shellers and corn grinders used by 14 farmer groups, and inefficient. To overcome this, a new machine is needed to peel and grind corn with the results of whole corn cobs. The goal is to simplify the work of the farmers, increase the productivity of corn flour production and save costs. The method used in this training by demonstrating how to peel and grind corn using a machine. The women farmer group participated in the training with enthusiasm and at the end of the activity they were able to use the corn sheller and grinder, correctly. The community service team also donated corn shellers and grinders to partners.